DiatOmicBase: a versatile gene‐centered platform for mining functional omics data in diatom research - Villar, Emilie; Zweig, Nathanaël; Vincens, Pierre; Cruz de Carvalho, Helena; Duchene, Carole; Liu, Shun; Monteil, Raphael; Dorrell, Richard G.; Fabris, Michele; Vandepoele, Klaas; Bowler, Chris; Falciatore, Angela (The Plant journal : for cell and molecular biology, 2025)
SUMMARY Diatoms are prominent microalgae found in all aquatic environments. Over the last 20 years, thanks to the availability of genomic and genetic resources, diatom species such as Phaeodactylum tricornutum and Thalassiosira pseudonana have emerged as valuable experimental model systems for exploring topics ranging from evolution to cell biology, (eco)physiology, and biotechnology. Since the first genome sequencing projects initiated more than 20 years ago, numerous genome‐enabled datasets have been generated, based on RNA‐Seq and proteomics experiments, epigenomes, and ecotype variant analysis. Unfortunately, these resources, generated by various laboratories, are often in disparate formats and challenging to access and analyze. Here we present DiatOmicBase, a genome portal gathering comprehensive omics resources from P. tricornutum and T. pseudonana to facilitate the exploration of dispersed public datasets and the design of new experiments based on the prior‐art. DiatOmicBase provides gene annotations, transcriptomic profiles and a genome browser with ecotype variants, histone and methylation marks, transposable elements, non‐coding RNAs, and read densities from RNA‐Seq experiments. We developed a semi‐automatically updated transcriptomic module to explore both publicly available RNA‐Seq experiments and users' private datasets. Using gene‐level expression data, users can perform exploratory data analysis, differential expression, pathway analysis, biclustering, and co‐expression network analysis. Users can create heatmaps to visualize pre‐computed comparisons for selected gene subsets. Automatic access to other bioinformatic resources and tools for diatom comparative and functional genomics is also provided. Focusing on the resources currently centralized for P. tricornutum, we showcase several examples of how DiatOmicBase strengthens molecular research on diatoms, making these organisms accessible to a broad research community. Significance Statement In recent years, diatoms have become the subject of increasing interest because of their ecological importance and their biotechnological potential for natural products such as pigments and polyunsaturated fatty acids. Here, we present an interactive web‐based server that integrates public diatom omics (genomics, transcriptomics, epigenomics, proteomics, sequence variants) data to connect individual diatom genes to broader‐scale functional processes.